Monetary Policy Shocks and Business Cycle Fluctuations in a Small Open Economy: Sweden 1986-2002 - Jesper Lindé (Sveriges Riksbank, 2003)
This paper contains an empirical analysis of the dynamic effects of monetary policy on Swedish data within a framework consistent with the theoretical New-Keynesian type of small open economy models. Because of what appears to be time-varying seasonal patterns in the data, I argue that it is of crucial importance to use the annual inflation rate rather than the quarterly inflation rate in the empirical analysis. After a monetary policy shock, the impulse response functions for output and inflation display a hump-shaped pattern with peak effects after 1.5 - 2 years. There also seems to be considerable inertia in the real exchange rate. Sensitivity analysis suggests that the shape of the obtained impulse response functions is fairly robust with respect to the number of lags in the VAR, sample size, and the formulation of the policy rule. Also, we find evidence that foreign shocks are very important for understanding Swedish business cycles. In particular, they account for a large fraction of the lower frequency movements in output and inflation, whereas domestic shocks generate most of the high frequency movements in the data.
Keywords: C22; C52; E52; 330; Monetary policy shocks; Impulse response functions; VAR models; New-Keynesian models; Real exchange rates; Business cycles